Relationship of Halal Labels and Product Quality With Purchase Decision on Wardah Cosmetic Products - Maghfiroh, Mamluatul; Indrarini, Rachma (International Journal of Transdisciplinary Knowledge, 2023)
The Indonesian cosmetic industry’s development is relatively rapid because cosmetic products have become primary needs in Indonesia which the population is predominantly Muslim. This development caused competitive competition between cosmetics brands in Indonesia. Because of this competition, Wardah cosmetics is considering the halal label in its products and its quality to increase consumer purchasing decisions. This research uses quantitative methods that are associative. It aims to investigate the relationship between halal labels and product quality with the purchasing decision of Wardah cosmetics, especially in Surabaya. The number of samples used is 100 Muslim respondents who used Wardah cosmetics products in Surabaya. The data analysis technique used is multiple correlation coefficient analysis using SPSS version 25. The study results showed that halal labeling and product quality simultaneously had a significant and robust relationship with Wardah cosmetic products’ purchasing decisions. While partially, the halal labels and product quality had a moderate and considerable relationship with Wardah cosmetics products’ purchase decision.